Flavonoid-mediated biofilm inhibition and toxicological evaluation of Atriplex laciniata against multidrug-resistant MRSA - Almutairy, Bandar (Frontiers in Pharmacology, 2025)
Multidrug-resistant (MDR) superbugs threaten the efficacy of antibiotics, so new drug formulations from synthetic or natural sources are needed to combat antimicrobial-resistant (AMR) infections. Traditional herbs are often considered alternatives for treating AMR and MDR infections. The present study involves evaluations of the efficacy and safety of Atriplex laciniata aqueous (AL-Aq-Ext) and flavonoid-rich (AL-Flv-Ext) extracts against MDR MRSA strains. The efficacies of the extracts against MRSA were tested for bacterial viability and biofilm inhibition through the MTT assay, OD600 nm measurements, confocal laser scanning microscopy (CLSM) for morphological observations, and amyloid-staining Congo-red phenotypic method. The safety of each extract was evaluated through comprehensive toxicological assessments, including acute toxicity, tissue biocompatibility, vital organ toxicity, and relative hemolysis. The results indicate MRSA cell viability at minimum inhibitory concentrations (MICs) of 512 μg/mL for AL-Aq-Ext and 256 μg/mL for AL-Flv-Ext. At these MICs, the extracts also exhibited bactericidal effects with zones of inhibition of 22 mm for AL-Aq-Ext and 20 mm for AL-Flv-Ext, which are comparable to the 25 mm for vancomycin. Both extracts showed more than 90% biofilm inhibition, which were confirmed through OD600 nm measurements, morphological detection based on reduction in fluorescence intensities via CLSM, and phenotype by the Congo-red amyloid-staining assay. The time-kill kinetics assays indicated prolonged bactericidal effects lasting approximately 73 h against MRSA. In terms of safety, acute toxicity studies were conducted by administering MIC doses of AL-Aq-Ext and AL-Flv-Ext orally to mice over 10 d, which revealed 100% survival rates and no immediate adverse effects. Histopathological analysis of the vital organs (liver and kidneys) showed no tissue damage, confirming the absence of acute organ toxicity; hemolysis assays demonstrated no red blood cell lysis at any tested concentration, indicating excellent blood compatibility. These findings demonstrate that A. laciniata extracts (AL-Aq-Ext and AL-Flv-Ext) are rich in flavonoids, safe, biocompatible, and suitable for further pharmacological development, with promising potential for preclinical and clinical trials. However, the present study is limited to acute toxicity and short-term exposure evaluations; hence, future research should focus on identifying specific bioactive compounds, evaluating the long-term toxicities, studying the pharmacokinetics, assessing the efficacies in disease models, and investigating potential immunogenicity and drug interactions to fully establish the therapeutic potential of the extracts.